2017
DOI: 10.1590/1678-457x.00717
|View full text |Cite
|
Sign up to set email alerts
|

Composted slaughterhouse sludge as a substitute for chemical fertilizers in the cultures of lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.)

Abstract: Flotation sludge (FS) is produced in huge amounts at slaughterhouses in western Santa Catarina, Brazil. This waste is rich in plant nutrients and a valuable resource for soil amendments. Five FS composts were tested as a replacement for chemical fertilizers (QF), namely T1 (75% poultry manure (PM) and 25% sawdust (SD)); T2 (50% PM and 50% SD); T3 (25% PM and 75% SD); T4 (100% PM and 0% SD); and T5 (0% PM x 100% SD). For lettuce plants, treatments containing composted FS resulted in an increased number of leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The tested materials were pig slaughterhouse sludge from a primary wastewater treatment system (coagulation, flocculation and centrifugation), eucalyptus sawdust from local logging companies and a stabilizing compost (used as an inoculum). These materials were mixed for composting in five treatments, all including a fixed 50% sawdust as the bulking agent and the main source of carbon: T1: sawdust and slaughterhouse sludge (50:50, v:v) was the control, since it was considered efficient in previous studies, based on physical-chemical stabilization [26] and absence of phytotoxicity [27]. T2: sawdust, slaughterhouse sludge and meal from dead pigs (50:20:30).…”
Section: Composting and Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested materials were pig slaughterhouse sludge from a primary wastewater treatment system (coagulation, flocculation and centrifugation), eucalyptus sawdust from local logging companies and a stabilizing compost (used as an inoculum). These materials were mixed for composting in five treatments, all including a fixed 50% sawdust as the bulking agent and the main source of carbon: T1: sawdust and slaughterhouse sludge (50:50, v:v) was the control, since it was considered efficient in previous studies, based on physical-chemical stabilization [26] and absence of phytotoxicity [27]. T2: sawdust, slaughterhouse sludge and meal from dead pigs (50:20:30).…”
Section: Composting and Raw Materialsmentioning
confidence: 99%
“…Nonetheless, the efficiency of composting cannot be evaluated considering only a single property, since physicochemical analyses and phytotoxicity assays are also relevant [25]. The efficiency of the composting treatments including sludge from agro-industrial wastewater treatment systems and sawdust was already reported [26,27]. However, considering that composts generated from treatments including meal from dead pigs may contribute to attenuate the dependence of agriculture on chemical fertilizers, the effects of the inclusion of such meals on the nutrient content and maturity of composts still needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Lakhiar et al [21] concluded that the highest TPC values were achieved in air-assisted atomizer. TFC is mainly responsible for the antioxidants of food and leafy vegetables have higher values of it when cultivated in air-circulation system [54,56,57] . The antioxidant activity depends on the species, geographic origin, agricultural practices used, and cultivation systems [58] .…”
Section: Discussionmentioning
confidence: 99%
“…Curly lettuce is a fresh vegetable consumed alone or in combination with other vegetables ready for consumption, usually consumed in mixed and fresh-cut salads. Depending on the leaf type and growing conditions, its edible leaves present high demand for nutrients (El-Nakhel et al, 2019;Oliveira et al, 2018;Patella et al, 2019).…”
Section: Introductionmentioning
confidence: 99%